Green Accounting Practice Model for Tourism Villages in Support of Sustainable Tourism in Bali - Astawa, I Putu; Arya Astawa, I Nyoman Gede; Ardina, Cening; Novandra Asta, Ngr. Putu Raka (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2025)
Tourism is currently in the spotlight because the massive use of natural resources is rumored to damage the order of life in the future. Various efforts are made for tourism business actors to maintain sustainability so that this nature remains sustainable. Information on sustainability activities is very important to be known by all parties to legitimize the implementation of sustainability. This research provides information on the implementation of sustainability practices in tourist villages with the main objective of designing a financial transaction model based on green accounting practices that have not been widely practiced in a tourist destination in the village. A qualitative approach was used to dig deeper into the data from five informants of tourist village managers who have implemented sustainability. The results of the study explain that transactions related to the environment are recorded, recognition of costs incurred, measurement, recording to accounts, then presented and detailed disclosure of environmental costs. In addition, it was found that environmental prevention costs, environmental detection costs and internal failure costs in strengthening sustainable tourism. The results of the study contribute to accounting science in revealing an environmental cost aimed at supporting sustainable tourism. This condition is a new way of maintaining sustainability oriented on financial transactions. This research can be developed quantitatively in strengthening the green accounting model associated with sustainable tourism.